Exploring the usefulness of comprehensive care plans for children with medical complexity (CMC): a qualitative study - Adams Sherri; Cohen Eyal; Mahant Sanjay; Friedman Jeremy N; MacCulloch Radha; Nicholas David B (BMC, 2013)
Abstract Background The Medical Home model recommends that Children with Special Health Care Needs (CSHCN) receive a medical care plan, outlining the child's major medical issues and care needs to assist with care coordination. While care plans are a primary component of effective care coordination, the creation and maintenance of care plans is time, labor, and cost intensive, and the desired content of the care plan has not been studied. The purpose of this qualitative study was to understand the usefulness and desired content of comprehensive care plans by exploring the perceptions of parents and health care providers (HCPs) of children with medical complexity (CMC). Methods This qualitative study utilized in-depth semi-structured interviews and focus groups. HCPs (n = 15) and parents (n = 15) of CMC who had all used a comprehensive care plan were recruited from a tertiary pediatric academic health sciences center. Themes were identified through grounded theory analysis of interview and focus group data. Results A multi-dimensional model of perceived care plan usefulness emerged. The model highlights three integral aspects of the care plan: care plan characteristics, activating factors and perceived outcomes of using a care plan. Care plans were perceived as a useful tool that centralized and focused the care of the child. Care plans were reported to flatten the hierarchical relationship between HCPs and parents, resulting in enhanced reciprocal information exchange and strengthened relationships. Participants expressed that a standardized template that is family-centered and includes content relevant to both the medical and social needs of the child is beneficial when integrated into overall care planning and delivery for CMC. Conclusions Care plans are perceived to be a useful tool to both health care providers and parents of CMC. These findings inform the utility and development of a comprehensive care plan template as well as a model of how and when to best utilize care plans within family-centered models of care.